Economic growth, labour flexibilization and employment quality in Colombia, 2002-11. - FARNÉ, Stefano; VERGARA, Carlos Andrés (International Labour Review, 2015)
Over the period 2002-11, the Colombian labour market saw a marked improvement in employment opportunities, accompanied by an increase in nonstandard forms of employment. The authors look at how this affected employment quality, using a composite index based on Categorical Principal Components Analysis (CATPCA). They observe a small but widespread improvement in employment quality - mainly for self-employed women - brought about by higher earnings, increased social protection and less time-related underemployment. However, a considerable 'quality deficit' remains, which calls for policies to strengthen labour market institutions and stimulate productivity and investment.